2022
DOI: 10.3389/fimmu.2021.820126
|View full text |Cite
|
Sign up to set email alerts
|

Impact on HIV-1 RNA Levels and Antibody Responses Following SARS-CoV-2 Vaccination in HIV-Infected Individuals

Abstract: This study aims to assess the immunological response and impact on virological control of the mRNA vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among people living with HIV (PLWH). In this single-center observational study, all PLWH were offered vaccination with mRNA1273 or BNT162b2. Both anti-N and anti-S1-receptor binding domain (RBD) antibodies were measured together with HIV-1 RNA levels after the first dose (M0) and then at 1 (M1), 2 (M2) and 6 (M6) months later. A total of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 13 publications
2
31
1
Order By: Relevance
“…Interestingly, anti-spike plasma IgG titers were still significant after 6 months post priming compared to baseline in most patients. Differently from what observed by Portillo and colleagues for anti-RBD antibodies, we did not find any statistical difference when comparing PLWHIV antibody titres to the HCs at all time-points, though it could be influenced by the different assay technology or different mRNA formulations (17). More than 80% of the percentage of PLWHIV showed a positive ACE2/RBD inhibition activity at +60 v2, that declined up to 54% at +150 v2.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, anti-spike plasma IgG titers were still significant after 6 months post priming compared to baseline in most patients. Differently from what observed by Portillo and colleagues for anti-RBD antibodies, we did not find any statistical difference when comparing PLWHIV antibody titres to the HCs at all time-points, though it could be influenced by the different assay technology or different mRNA formulations (17). More than 80% of the percentage of PLWHIV showed a positive ACE2/RBD inhibition activity at +60 v2, that declined up to 54% at +150 v2.…”
Section: Discussioncontrasting
confidence: 99%
“…Immunological studies on healthy subjects vaccinated with nanoparticles-based mRNA formulations (12) clearly show the persistence of circulating Spike-specific antibodies and immune memory cells at least after six months from vaccination (13,14). Up to date, longitudinal data regarding SARS-CoV-2 vaccine humoral response in PLWHIV do not suggest a reduced persistence of circulating antibody compared to healthy subjects (15)(16)(17). However, considering HIV-induced immunological impairments (18), It is of primary importance to investigate the induction and persistence of spike-specific memory B cells in PLWHIV upon vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also reported consistently lower antibody titer level post-vaccination for PLWH at multiple time points; however, the median age of PLWH in the study was 54 years compared to 30 years in the comparators ( 24 ). Their results could have been affected by age imbalance between the groups since evidence suggests older individuals have lower quantitative anti-spike IgG after vaccination ( 25 ).…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies reported no correlation between undetectable plasma HIV viremia, conventionally defined as plasma HIV RNA lower than 20 copies/mL [ 22 ] or 30 copies/mL [ 23 ], and humoral response, so we planned to separately evaluate the impact of persistent plasma HIV RNA complete suppression, defined as confirmed undetectable plasma HIV RNA versus low level HIV viremia, to show if absence of clinically quantifiable ongoing viremia could influence response to the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%